(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
This article analyzes the role of innovative technologies in the lesson. As it is known, today the theory and practice of language and culture attract more and more scholars; it has become evident that the investigation of its problems requires expertise from the different points of view of various areas of linguistics.